Value of MR elastography for the preoperative estimation of liver regeneration capacity in patients with hepatocellular carcinoma. Issue 6 (16th November 2016) - Jang, Siwon; Lee, Jeong Min; Lee, Dong Ho; Joo, Ijin; Yoon, Jeong Hee; Chang, Won; Han, Joon Koo
Abstract : Purpose: To demonstrate the negative relationship between liver stiffness (LS) values measured at preoperative magnetic resonance elastography (MRE) and the regeneration capacity of the remnant liver after major hepatectomy, in patients with hepatocellular carcinoma (HCC). Materials and Methods: Thirty‐eight patients with HCC (mean age, 57.1) who had undergone liver computed tomography (CT) and 1.5T MRE prior to right hepatectomy were included in this retrospective study. CT volumetric analysis of total functional liver (calculated by subtracting tumor volume from total liver volume), future liver remnant (FLR), and postoperative liver remnant (LR) were performed using a semiautomatic analysis program. The regeneration index was expressed as [(VLR ‐VFLR )/VFLR ] × 100, where VLR is the volume of the liver remnant and VFLR is the volume of the FLR. The relationship between degree of LS measured at MRE and the regeneration index was assessed using the Spearman correlation test. Results: Average LS value at MRE increased along with hepatic fibrosis (HF) stage ( r  = 0.604, P < 0.001). At MRE, a cutoff value greater than 2.46 kPa yielded 90.0% sensitivity and 100% specificity in identifying HF stage 2 or greater (area under the curve [AUC], 0.95). Mean VFLR and VLR were 477.1 ± 147.5 mL and 911.9 ± 188.8 mL, respectively. The regeneration index of the liver remnant was 102.1 ± 58.2%. LS values at MRE and calculated regeneration index after right hepatectomy showed moderate negative correlation ( r  = –0.361, P  = 0.026). Conclusion: LS values measured at MRE may serve as a postoperative predictor of liver regeneration in patients with liver cirrhosis and HCC. Level of Evidence : 4 Technical Efficacy : Stage 2 J. MAGN. RESON. IMAGING 2017;45:1627–1636